ANALISIS PENGARUH KUALITAS PRODUK DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN, DAN SIKAP TERHADAP MEREK SERTA DAMPAKNYA TERHADAP MINAT WORD OF MOUTH PADA MINUMAN PENAMBAH TENAGA SERBUK HEMAVITON JRENG (Studi Kasus PadaMasyarakat di Kecamatan Tembalang - Kusumo, Dimas Adhi; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research is to analyze the effect of product quality, customer value,and brand attitude to word of mouth intention by using a variable customer satisfaction as intervening on consumer Hemaviton Jreng in Tembalang sub-district.The population in this study is consumers Hemaviton Jreng who live in Tembalang sub-district. The sample in this study are 150 respondents by using purposive sampling method. Analyzer whom used in this research is SEM (Structural Equation Modeling) via AMOS 20.0The results showed that product quality and brand attitude has positiveÂ and significantÂ effect on customer satisfaction, variable product quality, customervalue, brand atiitude and customer satisfaction has positive and significant effect on word of mouth intention, and customer value has no effect on customer satisfaction